'Coping with Christmas'- a group intervention for bereaved children. Issue 3 (2nd September 2017) - Killick, Steve; Feeney, James; Rhinehart, Molly
Abstract: This paper outlines a day-long group intervention for children over the Christmas period who have experienced the loss of a family member. Christmas can be a painful time for children and families as intense feelings of grief may emerge and can be difficult to manage. Group interventions with bereaved children have been demonstrated to be effective and a group intervention was developed that encouraged Christmas to be seen as a time for remembrance, enjoyment and for the development of coping skills. The content and structure of the group is described. Findings from evaluations are reported and issues about the intervention are discussed.